Overcoming Problems Combination of Server and Client Side Encryption on Web Code Security Using the Slice Code Method - Kamarudin .; Fajar Akbar Maulana (Jurnal Riset Sistem dan Teknologi Informasi, 2023)
Web security protection that is carried out by some web developers is to protect the source code of web applications by encrypting the source code, both the source code that runs on the web server or the source code that runs on the client browser. Combining these two encryption technologies is a problem for web developers. If using server side encryption, the client side source code is not protected. However, if you use client-side encryption, the server source code becomes unreadable by the web server. This study aims to overcome the problem of the combination of these two encryption technologies, so the Slice Code method is used, which is a method that the researchers themselves have developed and used to encrypt server and client source code simultaneously and combine the two. With this method, the original source code is separated into 2 parts, then the pure client source code is encrypted using client encryption technology, then embedded into the pure server source code. The next step is to encrypt the pure server source code. The result is that web applications can run perfectly by having source code encryption from both sides, namely the server side and the client side